x^2=8x-17
x^2-8x+17=0
Д=(-8)^2-4*17=64-68 <0
14x=-49-x^2
X^2+14x+49=0
D=14^2-4*49=196-196=0
x=-14/2=-7
36+17x=-2x^2
2x^2+17x+36=0
D=17^2-4*2*36=289-288=1
x1=-17+1/4=-16/4=-4
x2=-17-1/4=-18/4
7x^2-3x=4
7x^2-3x-4=0
D=-3^2+4*7*4=9+112=121=11^2
x1=3+11/14=1
x2=3-11/14=-8/14
0.81-x^2=0
-x^2=-0.81
x^2=0.81
x=+-0.9
5x+9x^2=0
9x^2+5x=0
x(9x+5)=0
x=0 9x=-5
x=-5/9
1+2x=8x^2
-8x^2+2x+1=0
D=2^2+4*8=4+32=36=6^2
x1=-2+6/-16=-1/4
x2=-2-6/-16=1/2
19x-6x^2-10=0
-6x^2+19x-10=0
D=19^2-4*6*10=361-240=121=11^2
x1=-19+11/-12=-8/-12=2/3
x2=-19-11/-12=2.5
8+2x^2=0
2x^2=-8
x^2=-4 нет корней
40x-25-16x^2=0
-16x^2+40x-25=0
D=40^2-4*16*25=1600-1600=0
x=-40/-32=10/8=5/4
-36-x^2=-12x
-x^2+12x-36=0
D=12^2-4*36=144144=0
x=-12/-2=6
x^2-8x+17=0 => D=64-4*17 = Р Н
4x=-49-x^2 => x^2+4x+49=0 => D=16-4*49=Р Н
36+17x=2x^2 => 2x^2+17x+36=0 =>D=289-288=1 => x1=-9/2 => x2=-4
7x^2-3x=4 = > D9-4*7*(-4)=121 => x1=1 => x2=-9/14
x^2=81 = > x=+-9
5x+9x^2=0 => x(5+9x)=0 =>x=0 или x=-5/9
1+2x=8x^2 => 8x^2-2x-1=0 => D=4-4*8*(-1)=36 => x1=1/2 => x2=-1/4
19x-6x^2-10=0 =>6x^2-19x+10=0 =>D=361-4*6*10=121 =>x1=30/38 => x2=8/38
8+2x^2=0 => 2x^2=-8 => x^2=-4 => x=Р Н
40x-25x^2+12x=0 => 28-25x^2=0 =>x(28-25x)=0 => x=0 или 25x=28 => x=28/25
3х+2у=4 5х+у=9 у=9-5х 2х-9+5х=5 7х=14 х=2 у=-1
2. x^2-y^2=3 (x-y)(x+y)=3 3(x+y)=3 x+y=1 x=1-y
x-y=3 1-y-y=3 -2y=2 y=-1 x-(-1)=3 x=2
3/ x+y=1 x=1-y
xy=-2 y-y^2=-2 y^2-y=2 (y-0,5)^2-0,25=-2 (y-0,5)^2=2,25 y-0,5= 1,5 =-1,5
y=2 x=-1
y=-1 x=2
4,5 аналогично 2